Constitutional aspects of provisional enforcement, the duties of the President of the Republic of Poland by the Marshal of the Sejm - Walczuk, Konrad (Management and Administration Journal, 2023)
The Republic of Poland shall be a democratic state ruled by law and one of the main constitutional principles is the principle of the separation and balancing of power. Thus, the President of the Republic of Poland (considered to be the executive) and Marshal of the Sejm (belongs to thelegislative branch) are entities that have in their activities to balance each other, which in practice can and should lead to reciprocal limitation. In addition, the President of the Republic of Poland and the Marshal of the Sejm have different delegation sovereign (the Nation) to rule in his name. Only the President of the Republic is elected by a sovereign right to exercise a particular function - the head of state, while a person becoming Marshal of the Sejm is indicated only by the Nation as deputy, and only just as a deputy is appointed by the other deputies to act as Marshal of the Sejm. As a result, a situation in which the Marshal of the Sejm temporarily perform the duties of head of state is absolutely extraordinary situation. Although it seems there is no need for more extensive constitutional regulation of this situation, because at that time particularly important are habits and practices in the application of the Constitution (forming legal culture), and a relatively high degree left field for action politicians who are supposed to be later judged by voters who are voice of sovereign.However, we need more regulation than the current level to ensure the safety of State and citizens, including by clarifying procedures for taking power. Although it is expected restraint from the Marshal of the Sejm, who found himself in a situation where he have to replace the head of state, without becoming it. Even if the element limiting the action will be only relatively difficult to definable legal culture.